Pengaruh Profitabilitas, Ukuran Perusahaan, Leverage, Komite Audit dan Komisaris Independen terhadap Agresivitas Pajak: Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di BEI Tahun 2021-2023 (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to investigate the effect of Profitability, Company Size, Leverage, Audit Committee, and Independent Commissioners on Tax Aggressiveness in mining sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. Tax aggressiveness is a practice carried out by companies to minimize their tax obligations, either through legal (tax avoidance) or illegal (tax evasion) strategies. This study uses a quantitative approach with data analysis obtained from the financial statements of companies listed on the IDX. The variables tested include Profitability as measured by Return on Assets (ROA), Company Size as measured by the logarithm of total assets, Leverage as measured by Debt to Equity Ratio (DER), Audit Committee as calculated based on the number of committee members, and Independent Commissioners as calculated based on the proportion of independent commissioners in the board of commissioners. The results of the study indicate that Profitability and Company Size have a negative effect on Tax Aggressiveness, which means that companies with higher profitability and large company sizes tend to be less aggressive in their tax planning. Leverage, Audit Committee, and Independent Commissioners are also proven to have a negative effect on Tax Aggressiveness, indicating that companies with better oversight structures tend to be more compliant with tax obligations. These findings contribute to the development of Corporate Governance and Taxation theory, as well as providing recommendations to regulators and companies to improve oversight and transparency in financial and tax reporting.